Application of a ?Big-Tree? model to regional climate modeling: a sensitivity study - X.-M. Zeng; M. Zhao; R.-C. Yu; N.-S. Lin; Y.-Q. Zheng; L.-J. Zhang; R.-J. Zhang (Theoretical and Applied Climatology, 2003)

Regeneration and large-scale propagation of Phragmites communis through somatic embryogenesis - Ying-Gen Yang; Yi-Ming Guo; Yi Guo; Zhong-Chen Guo; Jin-Xing Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

In Vitro Simulation of Solid-Solid Dehydration, Rehydration, and Solidification of Trehalose Dihydrate Using Thermal and Vibrational Spectroscopic Techniques - Shan-Yang Lin; Jui-Lung Chien (Pharmaceutical Research, 2003)

Evidence of a founder effect for the 235delC mutation of GJB2 (connexin26) in east Asians - Denise Yan; Hong-Joon Park; Xiao Mei Ouyang; Arti Pandya; Katsumi Doi; Raadnabazar Erdenetungalag; Li Lin Du; Naoki Matsushiro; Walter E. Nance; Andrew J. Griffith; Xue Zhong Liu (Human Genetics, 2003)

Distribution and Risk Assessment of Fluoride in Drinking Water in the West Plain Region of Jilin Province, China - Zhang Bo; Hong Mei; Zhao Yongsheng; Lin Xueyu; Zhang Xuelin; Dong Jun (Environmental Geochemistry and Health, 2003)

QSARs for Predicting the Toxicity of Mixtures Containing Polar Narcotic Chemicals - Z. Lin; K. Yin; C. Wu; L. Wang; H. Yu (Bulletin of Environmental Contamination and Toxicology, 2003)

Spontaneous clearance of high-titer serum HBV DNA and risk of hepatocellular carcinoma in a Chinese population - Rebecca A. Harris; Gang Chen; Wen Yao Lin; Fu Min Shen; W. Thomas London; Alison A. Evans (Cancer Causes & Control, 2003)

Monitoring the polysaccharide quality of Agaricus blazei in submerged culture by examining molecular weight distribution and TNF-α release capability of macrophage cell line RAW 264.7 - Chin-Hang Shu; Bor-Jiun Wen; Ko-Jung Lin (Biotechnology Letters, 2003)

A general map matching algorithm for transport telematics applications - Mohammed A. Quddus; Washington Yotto Ochieng; Lin Zhao; Robert B. Noland (GPS Solutions, 2003)

Identification of essential histidine residues in a recombinant ?-amylase of thermophilic and alkaliphilic Bacillus sp. strain TS-23 - Chen-Tien Chang; Huei-Fen Lo; Meng-Chun Chi; Chia-Yu Yao; Wen-Hwei Hsu; Long-Liu Lin (Extremophiles, 2003)

Occurrence and sequences of Lily mottle virus and Lily symptomless virus in plants grown from imported bulbs in Zhejiang province, China - H.-Y. Zheng; J. Chen; M.-F. Zhao; L. Lin; J.-P. Chen; J. F. Antoniw; M. J. Adams (Archives of Virology, 2003)

Multiple generations of pseudotachylyte in the brittle to ductile regimes, Qinling–Dabie Shan ultrahigh‐pressure metamorphic complex, central China - Aiming Lin; Zhiming Sun; Zhenyu Yang (Island Arc, 2003)
Pseudotachylytes are present along the Dahezhen shear zone in the Qinling–Dabie Shan collisional orogenic belt, central China. Two types of pseudotachylyte vein are documented in the shear zone: cataclasite‐related pseudotachylyte (C‐Pt) and mylonite‐related pseudotachylyte (M‐Pt). M‐Pt is associated with mylonite‐development and is overprinted by C‐Pt. All of the quartz and most of the feldspar porphyroclasts within the M‐Pt are plastically deformed, but not in the C‐Pt. Dynamically recrystallized fine‐grained quartz and feldspar bands are oriented subparallel to the mylonite and M‐Pt foliation, and partially surround the porphyroclasts. Our results suggest that the M‐Pt formed cyclically in the ductile region at estimated conditions of 400–650°C and 400–800 MPa due to propagation of seismic fracturing associated with the thrusting‐related rapid exhumation of the ultrahigh‐pressure metamorphic complex in the brittle regime down to a greater depth than the base of the seismogenic zone. The M‐Pt and mylonite formed in the Dahezhen shear zone at estimated conditions of 400–650°C and 400–800 MPa. The coexistence of C‐Pt and M‐Pt in the same shear zone suggests that repeated seismic slips occurred in both the brittle and ductile portions of the crust during the thrusting‐related rapid exhumation of the ultrahigh‐pressure metamorphic complex.

Thermal field over Tibetan Plateau and Indian summer monsoon rainfall - Sanjay D. Bansod; Zhi‐Yong Yin; Zhenyao Lin; Xueqin Zhang (International Journal of Climatology, 2003)
The interannual variability of the temperature anomalies over the Tibetan Plateau (25–45 °N, 75–105 °E) is examined in relation to the Indian summer monsoon rainfall (ISMR: June to September total rainfall). For this purpose, the temperature anomaly data of the central‐eastern Tibetan Plateau is divided into three regions using principal component analysis and the ISMR data for the period 1957–89 have been used. It is found that the January temperature anomaly of Region 2 has a significant negative relationship ( r = −0.67) with the ISMR of the subsequent season. This region is located over the northeastern part of the Tibetan Plateau, mostly in Qinghai province, including the Bayan Harr Mountain range and the Qaidam Basin. This relationship is consistent and robust during the period of analysis and can be used to predict the strength of the Indian summer monsoon in the subsequent season. It was found that the January temperature anomaly in this region was associated with a persistent winter circulation pattern over the Eurasian continent during January through to March. Finally, the variation patterns of the temperature anomalies in all three regions over the central‐eastern Tibetan Plateau during extreme years of the ISMR are examined. It is concluded that the January temperature anomaly over the northeastern Tibetan Plateau can be useful in forecasting the drought and flood conditions over India, especially in predicting the monsoon rainfall over the areas lying along the monsoon trough. Copyright © 2003 Royal Meteorological Society

A rice transcription factor OsbHLH1 is involved in cold stress response - Yu-Jun Wang; Zhi-Gang Zhang; Xin-Jian He; Hua-Lin Zhou; Yu-Xiang Wen; Ji-Xun Dai; Jin-Song Zhang; Shou-Yi Chen (Theoretical and Applied Genetics, 2003)

Fine linkage mapping enables dissection of closely linked quantitative trait loci for seed dormancy and heading in rice - Y. Takeuchi; S. Y. Lin; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2003)

Cloning and characterization of leaf cDNAs that are differentially expressed between wheat hybrids and their parents - L. M. Wu; Z. F. Ni; F. R. Meng; Z. Lin; Q. X. Sun (Molecular Genetics and Genomics, 2003)

Surfactant proteinA and B genetic variants predispose to idiopathic pulmonary fibrosis - Moises Selman; Hung-Mo Lin; Martha Montao; Audrey L. Jenkins; Andrea Estrada; Zhenwu Lin; Guirong Wang; Susan L. DiAngelo; Xiaoxuan Guo; Todd M. Umstead; C. Max Lang; Annie Pardo; et al. (Human Genetics, 2003)

Annual Variations of Gonadotropin Content and Ovarian Development of Feral Female Catfish, Silurus asotus, in Central China - Hai Sh Wen; Hao R. Lin; Yu Z. Mao; Liang Wang; Ya P. Zhang (Environmental Biology of Fishes, 2003)

Role of tumor metastasis suppressor gene KAI1 in digestive tract carcinomas and cancer cells - Qiao Wu; Yuan Ji; Ming-qing Zhang; Yu-qiang Chen; Fu Chen; Da-lin Shi; Zong-hui Zheng; Yao-jian Huang; Wen-jin Su (Cell and Tissue Research, 2003)

Ground spider diversity in the Kenting uplifted coral reef forest, Taiwan: a comparison between habitats receiving various disturbances - Yu-Lung Hsieh; Yao-Sung Lin; I-Min Tso (Biodiversity and Conservation, 2003)

Historical biogeography and phylogenetic relationships of the genus Chamaecyparis (Cupressaceae) inferred from chloroplast DNA polymorphism - W. P. Wang; C. Y. Hwang; T. P. Lin; S. Y. Hwang (Plant Systematics and Evolution, 2003)

Plant regeneration through shoot formation from callus of Areca catechu L. - Hsiang-Chih Wang; Jen-Tsung Chen; Shieh-Ping Wu; Mei-Chun Lin; Wei-Chin Chang (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Cariporide enhances lactate clearance upon reperfusion but does not alter lactate accumulation during global ischaemia - H. Lin; M.-S. Suleiman (Pflügers Archiv - European Journal of Physiology, 2003)

The mechanism of honokiol-induced and magnolol-induced inhibition on muscle contraction and Ca 2+ mobilization in rat uterus - Yu-Cheng Lu; Hwei-Hsien Chen; Chien-Hsin Ko; Yi-Ruu Lin; Ming-Huan Chan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Novel mutations in the IRF6 gene for Van der Woude syndrome - Xiaofang Wang; Jiali Liu; Haibing Zhang; Mingzhen Xiao; Jinfeng Li; Chunling Yang; Xianjun Lin; Zizhong Wu; Landian Hu; Xiangyin Kong (Human Genetics, 2003)

A common IL-13 Arg130Gln single nucleotide polymorphism among Chinese atopy patients with allergic rhinitis - Min Wang; Zhi-Min Xing; Chao Lu; You-Xiang Ma; De-Lin Yu; Zheng Yan; Shen-Wu Wang; Li-Sheng Yu (Human Genetics, 2003)

Expression and production of bioactive human interleukin-18 in transgenic tobacco plants - Bin Zhang; Ying-Hua Yang; Yong-Ming Lin; Qing Rao; Guo-Guang Zheng; Ke-Fu Wu (Biotechnology Letters, 2003)

Making thin polymeric materials, including fabrics, microbicidal and also water-repellent - Jian Lin; Shashi K. Murthy; Bradley D. Olsen; Karen K. Gleason; Alexander M. Klibanov (Biotechnology Letters, 2003)

Sequence Analysis of the Complete Genome of Rice Black-Streaked Dwarf Virus Isolated from Maize with Rough Dwarf Disease - Zhao-Hui Wang; Shou-Guo Fang; Jia-Ling Xu; Li-Ying Sun; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2003)

Small-angle X-ray scattering measurement of the internal microstructure of natural zircon crystals - A. P. Radlinski; J. Claou-Long; A. L. Hinde; E. Z. Radlinska; J.-S. Lin (Physics and Chemistry of Minerals, 2003)

Solubility enhancement of a hydrophobic flavonoid, luteolin by the complexation with cyclosophoraoses isolated from Rhizobium meliloti - Sanghoo Lee; Dong-hyuk Seo; Hey-lin Park; Youngjin Choi; Seunho Jung (Antonie van Leeuwenhoek, 2003)

Evidence for the existence of some dissociation in an otherwise strong linkage disequilibrium between mitochondrial and chloroplastic genomes in Cyclobalanopsis glauca - T.‐P. Lin; W.‐J. Chuang; S. S. F. Huang; S.‐Y. Hwang (Molecular Ecology, 2003)
Variations in mitochondrial DNA in Cyclobalanopsis glauca (Thunb. ex Murray) Oerst. were studied in 140 trees from 32 populations collected from within the tree's natural range. By sequencing two mitochondrial DNA intron fragments ( nad 4/3 ‐nad 4/4r and nad 7/2 ‐nad 7/3r), we revealed a total of 1788 bp and five polymorphic sites which allowed us to distinguish six mitotypes. The mitochondrial DNA markers provided replicated data to support population phylogeographical scenarios suggested previously using chloroplastic DNA markers. The gene genealogical tree of mitochondrial DNA was partially congruent with the chloroplastic DNA tree owing to the slower mutation rate and different mutational direction. Significant linkage disequilibrium existed between the two organellar genomes. Further paring analyses between fragments synthesized using different primers, accompanied by exclusion of polymorphic sites, showed that the random association could be attributed specifically to one of the polymorphic sites of the pet G‐ trn P fragment of the chloroplastic genome, and the three polymorphic sites of the nad 4/3‐ nad 4/4r fragment of the mitochondrial genome. The former was inferred to derive from paternal leakage, and the latter from recurrent mutation. These polymorphic sites were also responsible for uncoupling of the combined gene tree of mitotype and chlorotype. In conclusion, specific fragments found in this study contribute to the incomplete congruence of the two organellar lineages that otherwise associate well phylogeographically.

Postglacial population growth of Cunninghamia konishii (Cupressaceae) inferred from phylogeographical and mismatch analysis of chloroplast DNA variation - Shih‐Ying Hwang; Tsan‐Piao Lin; Chiu‐Shun Ma; Chung‐Ling Lin; Jeng‐Der Chung; Jenq‐Chuan Yang (Molecular Ecology, 2003)
Phylogeographical and mismatch analysis of chloroplast DNA (cpDNA) variation were used to infer the temporal dynamics of distributional and demographic history of Taiwan fir ( Cunninghamia konishii ). We examined 64 and 52 trees from 17 populations of C. konishii and 14 provenances of C. lanceolata , respectively, by sequencing three intergenic spacers and one intron using cpDNA universal primers. Of the aligned 1888 base pairs (bp) sequence, 30 varied among 28 haplotypes, which consisted of three transitions, 14 transversions and 13 indels. One ancestral haplotype was found in 86 individuals across the surveyed range of both species, C. konishii and C. lanceolata , which was distributed in all populations and provenances. The 28 haplotypes also included 15 C. konishii specific and 12 C. lanceolata ‐specific haplotypes. Ancestral haplotype was found fixed in five populations of C. konishii and five provenances of C. lanceolata . Other haplotypes occurred mainly as singletons. The levels of population differentiation studied are relatively low in both Cunninghamia species. The nucleotide diversity ( θ ) of chloroplast DNA sequences within C. konishii was slightly higher than that of C. lanceolata . Excess in singletons as well as star‐like phylogeny of haplotypes suggested no clearcut migration patterns of C. konishii after glacial maximum. One probable demographic history of C. konishii is the postglacial population growth of C. konishii after a glacial bottleneck event. This inference is supported by the combined results of fossil pollen record, low nucleotide diversity, significant Tajima's d ‐value, phylogeographical analysis and unimodal mismatch distribution. Similarities and discrepancies between our results and those of Lu et al. (2001) are discussed.

Outbreaks of an iridovirus disease in maricultured large yellow croaker, Larimichthys crocea (Richardson), in China - X H Chen; K B Lin; X W Wang (Journal of Fish Diseases, 2003)

The blockade of formyl peptide-induced respiratory burst by 2',5'-dihydroxy-2-furfurylchalcone involves phospholipase D signaling in neutrophils - Jih-Pyang Wang; Ling-Chu Chang; Mei-Feng Hsu; Chun-Nan Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Application of MCR: Facile one-pot diastereoselective syntheses of novel chiral α,α'-iminodiacetic acid analogues - Kuangsen Sung; Fu-Lin Chen; Meng-Jung Chung (Molecular Diversity, 2003)

Regulation of distinct biological activities of the NF-?B transcription factor complex by acetylation - Lin-Feng Chen; Warner C. Greene (Journal of Molecular Medicine, 2003)

Strand Compositional Asymmetries of Nuclear DNA in Eukaryotes - Deng K. Niu; Kui Lin; Da-Yong Zhang (Journal of Molecular Evolution, 2003)

Nonrandom Intragenic Variations in Patterns of Codon Bias Implicate a Sequential Interplay Between Transitional Genetic Drift and Functional Amino Acid Selection - K. Lin; S. B. Tan; P. R. Kolatkar; R. J. Epstein (Journal of Molecular Evolution, 2003)

Ambulatory migration in mites (Acari: Tetranychidae, Phytoseiidae) to new leaves of moso bamboo shoots - Yanxuan Zhang; Yutaka Saito; Jianzhen Lin; Anthony R. Chittenden; Jei Ji; Yukie Sato (Experimental and Applied Acarology, 2003)

Relationship between CYP3A activity and breast cancer susceptibility in Chinese Han women - Ping Huang; Bing Zhu; Lian-Sheng Wang; Dong-Sheng Ouyang; Song-Lin Huang; Xiao-Ping Chen; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2003)

Determination of Organophosphorus Pesticides and Related Compounds in Water Samples by Membrane Extraction and Gas Chromatography - Pengxiang Xu; Dongxing Yuan; Shuming Zhong; Qingmei Lin (Environmental Monitoring and Assessment, 2003)

Toxicity of 21 Herbicides to the Green Alga Scenedesmus quadricauda - J. Ma; F. Lin; S. Wang; L. Xu (Bulletin of Environmental Contamination and Toxicology, 2003)

Prospective study of serum retinol, β-carotene, β-cryptoxanthin, and lutein/zeaxanthin and esophageal and gastric cancers in China - Christian C. Abnet; You-Lin Qiao; Sanford M. Dawsey; Dennis W. Buckman; Chung S. Yang; William J. Blot; Zhi-Wei Dong; Philip R. Taylor; Steven D. Mark (Cancer Causes & Control, 2003)

Novel Cu(II)-quinoline carboxamide complexes: Structural characterization, cytotoxicity and reactivity towards 5′-GMP - Junyong Zhang; Xiaokang Ke; Chao Tu; Jun Lin; Jian Ding; Liping Lin; Hoong-Kun Fun; Xiaozeng You; Zijian Guo (BioMetals, 2003)

Assessment of indirect use values of forest biodiversity in Yaoluoping national nature reserve, Anhui province - Hui Xu; Yi Qian; Lin Zheng; Bu-zhuo Peng (Chinese Geographical Science, 2003)

Type III secretion of EspB in enterohemorrhagic Escherichia coli O157:H7 - Hao-Jie Chiu; Wen-Shiun Lin; Wan-Jr Syu (Archives of Microbiology, 2003)

The change of North China climate in transient simulations using the IPCC SRES A2 and B2 scenarios with a coupled atmosphere-ocean general circulation model - Buhe Cholaw; Ulrich Cubasch; Lin Yonghui; Ji Liren (Advances in Atmospheric Sciences, 2003)

Dependence of Hurricane intensity and structures on vertical resolution and time-step size - Da-Lin Zhang; Xiaoxue Wang (Advances in Atmospheric Sciences, 2003)

A comparative study of conservative and nonconservative schemes - Lin Wantao; Wang Chunhua; Chen Xingshu (Advances in Atmospheric Sciences, 2003)

Tidal front and the convergence of anchovy ( Engraulis japonicus ) eggs in the Yellow Sea - Wei Hao; Su Jian; Wan Ruijing; Wang Lei; Lin Yi'an (Fisheries Oceanography, 2003)
Anchovy recruitment determines fish production and thus the sustainable exploitation of anchovy in the Yellow Sea. Haizhou Bay is a traditional spawning and nursery ground for anchovy. The retention of anchovy in its early life stages appears to be related to observed fronts. Cruises have confirmed that anchovy eggs are distributed in high density patches, particularly in the tidal frontal zone. Front and egg patches shift to the shallow area in the warm season. A diagnostic Hamburg Shelf Ocean Model was applied in the East China Sea and Yellow Sea to simulate the frontal circulation and particle movement, forced by monthly wind speed and measured temperatures. It was observed that the jet along the front and upwelling in the mixed side of the front play an important role in the transport of eggs. Convergence and divergence areas are frequently induced by frontal shear instability and topography potential vorticity balance. Numerical experiments show that tidal mixing and front play an important role to converge particles like eggs. When eggs are caught in the convergence zone they are aggregated into a patch. The convergence zone has good feeding condition for eggs to hatch and larvae to grow.

Actin filaments regulate the stretch sensitivity of large-conductance, Ca2+-activated K+ channels in coronary artery smooth muscle cells - Lin Piao; Won-Kyung Ho; Yung E. Earm (Pflügers Archiv - European Journal of Physiology, 2003)

Gene content and organization of an 85-kb DNA segment from the genome of the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; R. W. Hammond; R. Jomantiene; E. L. Dally; I.-M. Lee; H. Jia; H. Wu; S. Lin; P. Zhang; S. Kenton; F. Z. Najar; A. Hua; et al. (Molecular Genetics and Genomics, 2003)

The extent and distribution of linkage disequilibrium in a multi-hierarchic outbred canine pedigree - Xiang-Yang Lou; Rory J. Todhunter; Min Lin; Qing Lu; Tian Liu; Zuoheng Wang; Stuart P. Bliss; George Casella; Gregory M. Acland; George Lust; Rongling Wu (Mammalian Genome, 2003)

General Toxicity Prediction Approach for Mixtures Containing Polar Narcotic Chemicals - Z. Lin; C. Wu; P. Shi; L. Wang; S. Gao (Bulletin of Environmental Contamination and Toxicology, 2003)

Cold-active serine alkaline protease from the psychrophilic bacterium Pseudomonas strain DY-A: enzyme purification and characterization - Runying Zeng; Rui Zhang; Jing Zhao; Nianwei Lin (Extremophiles, 2003)

Characterization and purification of hydrolytic enzymes in Sinorhizobium fredii CCRC15769 - Chun-Yi Hu; Liang-Ping Lin (World Journal of Microbiology and Biotechnology, 2003)

Reinstatement of ethanol-seeking behavior by drug cues following single versus multiple ethanol intoxication in the rat: effects of naltrexone - Roberto Ciccocioppo; Daniel Lin; Rémi Martin-Fardon; Friedbert Weiss (Psychopharmacology, 2003)

The reinstatement model of drug relapse: history, methodology and major findings - Yavin Shaham; Uri Shalev; Lin Lu; Harriet de Wit; Jane Stewart (Psychopharmacology, 2003)

Disruption of plE2, the gene for the E2 subunit of the plastid pyruvate dehydrogenase complex, in Arabidopsis causes an early embryo lethal phenotype - Ming Lin; Robert Behal; David J. Oliver (Plant Molecular Biology, 2003)

A mixture model approach to detecting differentially expressed genes with microarray data - Chap T. Le; Wei Pan; Jizhen Lin (Functional & Integrative Genomics, 2003)

Detection ofBurkholderia pseudomallei in rice fields with PCR-based technique - C. M. Kao; S. C. Chen; Y. S. Chen; H. M. Lin; Y. L. Chen (Folia Microbiologica, 2003)

Operational Indicators for Measuring Agricultural Sustainability in Developing Countries - Lin Zhen; Jayant K. Routray (Environmental Management, 2003)

Overexpression, Purification, and Characterization of the Recombinant Leucine Aminopeptidase II of Bacillus stearothermophilus - Lih-Ying Kuo; Guang-Yuh Hwang; Yu-Jing Lai; Shin-Ling Yang; Long-Liu Lin (Current Microbiology, 2003)

Tropical Glacier and Ice Core Evidence of Climate Change on Annual to Millennial Time Scales - Lonnie G. Thompson; Ellen Mosley-Thompson; M. E. Davis; P.-N. Lin; K. Henderson; T. A. Mashiotta (Climatic Change, 2003)

Trace Metals in Chinese Joss Stick Smoke - T.-S. Lin; F.-M. Shen (Bulletin of Environmental Contamination and Toxicology, 2003)

Growth of Saccharomyces cerevisiae in a chemostat under high glucose conditions - Yupeng Zhao; Yen-Han Lin (Biotechnology Letters, 2003)

Propofol reduces nitric oxide biosynthesis in lipopolysaccharide-activated macrophages by downregulating the expression of inducible nitric oxide synthase - Ruei-Ming Chen; Gong-Jhe Wu; Yi-Ting Tai; Wei-Zen Sun; Yi-Ling Lin; Wen-Chi Jean; Ta-Liang Chen (Archives of Toxicology, 2003)

The decade-scale climatic forecasting in China - Lin Zhenshan; Shi Xiangsheng (Advances in Atmospheric Sciences, 2003)

Simulation of effects of land use change on climate in China by a regional climate model - Gao Xuejie; Luo Yong; Lin Wantao; Zhao Zongci; Filippo Giorgi (Advances in Atmospheric Sciences, 2003)

Seasonal characteristics of precipitation in 1998 over East Asia as derived from TRMM PR - Fu Yunfei; Lin Yihua; Guosheng Liu; Wang Qiang (Advances in Atmospheric Sciences, 2003)

Precipitation from vertical motion: a statistical diagnostic scheme - Brian E. J. Rose; Charles A. Lin (International Journal of Climatology, 2003)
The relationship between precipitation and atmospheric vertical motion is investigated over the globe. By combining and averaging precipitation rates within small ranges of vertical motion, the mean precipitation rate is found to vary smoothly with vertical motion. The relationship is modelled with a simple function that assumes zero precipitation for subsidence and linearly increasing precipitation for ascending motion. Function parameters are computed from National Centers for Environmental Prediction reanalysis data individually for every grid point and calendar month. Variations in the slope account for geographical and seasonal variations in moisture and other precipitation factors. At each grid point, the scheme diagnoses precipitation rate from a single concurrent value of vertical motion. It is shown to have moderate skill over climatology in predicting mean monthly precipitation. The midlatitudes, oceans and the winter season are favoured. The scheme is designed to extract precipitation fields from a dry general circulation model, based on the simulated vertical motion. Application to climate modelling is discussed. Copyright © 2003 Royal Meteorological Society

An efficient protocol for genomic DNA extraction fromCitrus species - Yun-Jiang Cheng; Wen-Wu Guo; Hua-Lin Yi; Xiao-Min Pang; Xiuxin Deng (Plant Molecular Biology Reporter, 2003)

A method for inflorescence proliferation - C.-S. Lin; C.-T. Chen; C.-C. Lin; W.-C. Chang (Plant Cell Reports, 2003)

Nuclear Transport by Laser-Induced Pressure Transients - Tai-Yuan David Lin; Daniel J. McAuliffe; Norm Michaud; Hong Zhang; Shun Lee; Apostolos G. Doukas; Thomas J. Flotte (Pharmaceutical Research, 2003)

Protective effects of daviditin A against endothelial damage induced by lysophosphatidylcholine - De-Jian Jiang; Jun-Lin Jiang; Gui-Shan Tan; Yan-Hua Du; Kang-Ping Xu; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Dissecting the pet18mutation in Saccharomyces cervisiae: HTL1encodes a 7-kDa polypeptide that interacts with components of the RSC complex - Y.-M. Lu; Y.-R. Lin; A. Tsai; Y.-S. Hsao; C.-c. Li; M. Y. Cheng (Molecular Genetics and Genomics, 2003)

Microwave-enhanced liquid-phase synthesis of thiohydantoins and thioxotetrahydropyrimidinones - Wen-Ben Yeh; Mei-Jung Lin; Ming-Juan Lee; Chung-Ming Sun (Molecular Diversity, 2003)

Photodegradation of Diesel Oil in Aqueous Solutions - P. Zhong; L. R. Kong; Z. F. Lin; G. M. Liu (Bulletin of Environmental Contamination and Toxicology, 2003)

Polychlorinated Biphenyls in Taiwanese Primipara Human Milk and Associated Factors - H.-R. Chao; S.-L. Wang; L.-Y. Lin; H.-Y. Yu; Y.-K. Lu; W.-L. Chou; Y.-L. Guo; L. W. Chang (Bulletin of Environmental Contamination and Toxicology, 2003)

Analysis of fMRI Data by Blind Separation of Data in a Tiny Spatial Domain into Independent Temporal Component - Huafu Chen; Dezhong Yao; Yan Zhuo; Lin Chen (Brain Topography, 2003)

Gully-specific debris flow hazard assessment in China - Xi-lin Liu (Chinese Geographical Science, 2003)

Strategies for agrobiodiversity conservation and promotion: a case from Yunnan, China - Chun-Lin Long; Heng Li; Zhiqin Ouyang; Xiangyun Yang; Qin Li; Bruce Trangmar (Biodiversity and Conservation, 2003)

The anabolic pyruvate oxidoreductase from Methanococcus maripaludis - Winston C. Lin; Yu-Ling Yang; William B. Whitman (Archives of Microbiology, 2003)

Seasonal changes in element contents in mangrove element retranslocation during leaf senescene - Wen-Qing Wang; Mao Wang; Peng Lin (Plant and Soil, 2003)

Genetic evidence for a role of phospholipase C at the budding yeast kinetochore - N. DeLillo; C. Romero; H. Lin; A. Vancura (Molecular Genetics and Genomics, 2003)

Genistein protects primary cortical neurons from iron-induced lipid peroxidation - Kwok Ping Ho; Lin Li; Li Zhao; Zhong Ming Qian (Molecular and Cellular Biochemistry, 2003)

Detection and analysis of QTLs for ferrous iron toxicity tolerance in rice, Oryza sativa L. - Jian-lin Wan; Hu-qu Zhai; Jian-min Wan; H. Ikehashi (Euphytica, 2003)

Conversion of an obligate autotrophic bacteria to heterotrophic growth: expression of a heterogeneous phosphofructokinase gene in the chemolithotroph Acidithiobacillus thiooxidans - Ke Li Tian; Jian Qun Lin; Xiang Mei Liu; Ying Liu; Chang Kai Zhang; Wang Ming Yan (Biotechnology Letters, 2003)

Detailed Computational Analysis of a Comprehensive Set of Group A Rotavirus NSP4 Proteins - Shuo Liang Lin; Peng Tian (Virus Genes, 2003)

Carbon sequestration in arid‐land forest - J. M. GRÜNZWEIG; T. LIN; E. ROTENBERG; A. SCHWARTZ; D. YAKIR (Global Change Biology, 2003)
Rising atmospheric CO 2 concentrations may lead to increased water availability because the water use efficiency of photosynthesis (WUE) increases with CO 2 in most plant species. This should allow the extension of afforestation activities into drier regions. Using eddy flux, physiological and inventory measurements we provide the first quantitative information on such potential from a 35‐year old afforestation system of Aleppo pine ( Pinus halepensis Mill.) at the edge of the Negev desert. This 2800 ha arid‐land forest contains 6.5 ± 1.2 kg C m −2 , and continues to accumulate 0.13–0.24 kg C m −2 yr −1 . The CO 2 uptake is highest during the winter, out of phase with most northern hemispheric forest activity. This seasonal offset offers low latitude forests ∼10 ppm higher CO 2 concentrations than that available to higher latitude forests during the productive season, in addition to the 30% increase in mean atmospheric CO 2 concentrations since the 1850s. Expanding afforestation efforts into drier regions may be significant for C sequestration and associated benefits (restoration of degraded land, reducing runoff, erosion and soil compaction, improving wildlife) because of the large spatial scale of the regions potentially involved (ca. 2 × 10 9 ha of global shrub‐land and C4 grassland). Quantitative information on forest activities under dry conditions may also become relevant to regions predicted to undergo increasing aridity.

Short-Term Sorption of Toluene Vapor onto Natural Organic Materials - Chuen-Huey Chiu; Tsair-Fuh Lin; Chiu-Chung Young (Water, Air, & Soil Pollution, 2003)

Selenium Removal from Irrigation Drainage Water Flowing Through Constructed Wetland Cells with Special Attention to Accumulation in Sediments - Suduan Gao; Kenneth K. Tanji; Douglas W. Peters; Zhiqing Lin; Norman Terry (Water, Air, & Soil Pollution, 2003)

Visibility Variation with Air Qualities in the Metropolitan Area in Southern Taiwan - Ying I. Tsai; Yi H. Lin; Suen Z. Lee (Water, Air, & Soil Pollution, 2003)

Comparison of soil nitrogen mineralization and nitrification in a mixed grassland and forested ecosystem in central Taiwan - Jeffrey S. Owen; Ming Kuang Wang; Hai Lin Sun; Hen Biau King; Chung Ho Wang; Chin Fang Chuang (Plant and Soil, 2003)

Ferredoxin from sweet pepper (Capsicum annuum L.) intensifying harpinpss-mediated hypersensitive response shows an enhanced production of active oxygen species (AOS) - Badri Venkata Dayakar; Hao-Jan Lin; Cheng-Hsien Chen; Mang-Jye Ger; Bor- Heng Lee; Chia-Hwei Pai; David Chow; Hsiang-En Huang; Shaw-Yhi Hwang; Mei-Chu Chung; Teng-Yung Feng (Plant Molecular Biology, 2003)

Noninvasive Characterization of Regional Variation in Drug Transport into Human Stratum Corneum in Vivo - Jui-Chen Tsai; Ching-Yu Lin; Hamm-Ming Sheu; Yu-Li Lo; Ying-Hsuan Huang (Pharmaceutical Research, 2003)

Stability and Release Performance of a Series of Pegylated Copolymeric Micelles - Wen-Jen Lin; Lee-Wei Juang; Chi-Chang Lin (Pharmaceutical Research, 2003)

Characterization of Fish Cu/Zn?Superoxide Dismutase and Its Protection from Oxidative Stress - Chuian-Fu Ken; Chi-Tsai Lin; Jei-Fu Shaw; Jen-Leih Wu (Marine Biotechnology, 2003)

Genetic Organization of Genes Encoding Phenol Hydroxylase, Benzoate 1,2-Dioxygenase Alpha Subunit and Its Regulatory Proteins in Acinetobacter calcoaceticus PHEA-2 - Yuquan Xu; Ming Chen; Wei Zhang; Min Lin (Current Microbiology, 2003)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

Cloning and expression of a new Tibetan hulless barley (Hordeum vulgare) β-1,3-glucanase gene - Zeng Yu; Xu Ying; Tang Lin; Qiang Xiao-Lin; Chen Fang (Biotechnology Letters, 2003)

Development of Linum flavum hairy root cultures for production of coniferin - Han-wei Lin; Kian H. Kwok; Pauline M. Doran (Biotechnology Letters, 2003)

Formation and water environmental evolution of the Nansihu Lake - Zhang Zulu; Shen Ji; Liu Enfeng; Sun Qingyi; Jiang Luguang; Wang Lin (Journal of Geographical Sciences, 2003)

Biotic communities of freshwater marshes and mangroves in relation to saltwater incursions: implications for wetland regulation - Hsing-Juh Lin; Kwang-Tsao Shao; Wen-Liang Chiou; Can-Jen W Maa; Hwey-Lian Hsieh; Wen-Lung Wu; Lucia L. Severinghaus; Yu-Tzu Wang (Biodiversity and Conservation, 2003)

Editorial: What is Molecular Diversity? - Shu-Kun Lin (Molecular Diversity, 2003)

Estradiol, aromatase and steroid receptors involved in the sex change of protandrous black porgy, Acanthopagrus schlegeli - Jin-Lien Du; Bih-Yun Lin; Yan-Hoarn Lee; Wen-Shiun Yueh; Chun-Lin He; Mong-Fong Lee; Lian-Tien Sun; Ching-Fong Chang (Fish Physiology and Biochemistry, 2003)

Activin stimulates goldfish FSH biosynthesis by enhancing FSHβ promoter activity - Wei Ge; Nga-Ling Ko; Flora Yee-Man Pang; Me-Fong Chung; Sze-Wah Lin; Chi-Wai Yuen; Man-Tat Lau; Lin Liu; Young Chang Sohn; Makito Kobayashi; Katsumi Aida (Fish Physiology and Biochemistry, 2003)

Inhibition of return in children with attention deficit hyperactivity disorder - Chiang-Shan Ray Li; Hsueh-Ling Chang; Shih-Chieh Lin (Experimental Brain Research, 2003)

Genetic relationships among cold, salt and drought tolerance during seed germination in an interspecific cross of tomato - M.R. Foolad; P. Subbiah; C. Kramer; G. Hargrave; G.Y. Lin (Euphytica, 2003)

A Thermodynamic Interpretation of the Monod Equation - Yu Liu; Yue-Mei Lin; Shu-Fang Yang (Current Microbiology, 2003)

Replacement of Methionine 208 in a Truncated Bacillus sp. TS-23 α-Amylase with Oxidation-Resistant Leucine Enhances Its Resistance to Hydrogen Peroxide - Long-Liu Lin; Huei-Fen Lo; Wen-Ying Chiang; Hui-Yu Hu; Wen-Hwei Hsu; Chen-Tien Chang (Current Microbiology, 2003)

Establishment of red fluorescent protein-tagged HeLa tumor metastasis models: Determination of DsRed2 insertion effects and comparison of metastatic patterns after subcutaneous, intraperitoneal, or intravenous injection - Jau-Yeong Lu; Hui-Chun Chen; Ricky Yuan-Yuan Chu; Tsu-Chun Emma Lin; Ping-I Hsu; Ming-Shyan Huang; Ching-Jiunn Tseng; Michael Hsiao (Clinical & Experimental Metastasis, 2003)

Cancer incidence patterns in Koreans in the US and in Kangwha, South Korea - Scarlett Lin Gomez; Gem M. Le; Christina A. Clarke; Sally L. Glaser; Anne-Marie France; Dee W. West (Cancer Causes & Control, 2003)

Naricolax insolitus n. sp., a bomolochid copepod (Poecilostomatoida) parasitic in the nasal cavities of silver pomfret Pampus argenteus off Taiwan - Ju-shey Ho; Ching-Long Lin (Systematic Parasitology, 2003)

Human infection by a swine influenza A (H1N1) virus in Switzerland - V. Gregory; M. Bennett; Y. Thomas; L. Kaiser; W. Wunderli; H. Matter; A. Hay; Y. P. Lin (Archives of Virology, 2003)

Nickel-induced oxidative stress and effect of antioxidants in human lymphocytes - Chang-Yu Chen; Yi-Fen Wang; Yu-Hwan Lin; Shu-Fang Yen (Archives of Toxicology, 2003)

Effect of Cadmium(Ii) and Anion Type on the Ageing of Ferrihydrite and its Subsequent Leaching under Neutral and Alkaline Conditions - Xiaomei Lin; Robert C. Burns; Geoffrey A. Lawrance (Water, Air, & Soil Pollution, 2003)

Increased crocin production and induction frequency of stigma-like-structure from floral organs of Crocus sativus L. by precursor feeding - Yuhong Zeng; Fang Yan; Lin Tang; Fang Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Effect of sucrose concentration on elongation of shoots from flax anther culture - Yurong Chen; Shirley Lin; Scott Duguid; Paul Dribnenki; Edward Kenaschuk (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Modulation of Digoxin Transport Across Caco-2 Cell Monolayers by Citrus Fruit Juices: Lime, Lemon, Grapefruit, and Pummelo - Jianguo Xu; Mei Lin Go; Lee-Yong Lim (Pharmaceutical Research, 2003)

Respiratory symptoms and lung-function changes with exposure to five substances in aluminium smelters - Lin Fritschi; Malcolm R. Sim; Andrew Forbes; Michael J. Abramson; Geza Benke; William A. Musk; Nicholas H. de Klerk (International Archives of Occupational and Environmental Health, 2003)

The contribution of size-fractionated plankton to biomass and primary production of phytoplankton in saline–alkaline ponds - Zhao Wen; Dong Shuang-Lin (Hydrobiologia, 2003)

Chloroplast Transformation in Oilseed Rape - Bing-Kai Hou; Yi-Hua Zhou; Li-Hong Wan; Zhong-Lin Zhang; Gui-Fang Shen; Zheng-Hua Chen; Zan-Min Hu (Transgenic Research, 2003)

Monogenea from the middle Yangtze Valley: Sinomazocraes changjiangensis n. g., n. sp. (Family Mazocraeidae Price, 1936) on a clupeiform fish from Hubei Province, China - Zhang Jianying; Liu Lin; Fang Jianping; Ding Xuejuan (Systematic Parasitology, 2003)

A list of monogeneans from Chinese marine fishes - Zhang Jianying; Yang Tingbao; Liu Lin; Ding Xuejuan (Systematic Parasitology, 2003)

Extensive polymorphism and different evolutionary patterns of intron 2 were identified in the HLA-DQB1 gene - Yonggui Fu; Zehuan Liu; Jianghai Lin; Weimin Chen; Zongjian Jia; Dejing Pan; Anlong Xu (Immunogenetics, 2003)

In vitro flowering of Bambusa edulis and subsequent plantlet survival - Chung-Chih Lin; Chuoun-Sea Lin; Wei-Chin Chang (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Erratum: Cloning and sequencing of the phycocyanin gene from Spirulina maxima and its evolutionary analysis - Ping Yu; Jian-Rong Li; Pei-Lin Cen; Song Qin; Fan Lin (Journal of Applied Phycology, 2003)

IDENTIFICATION AND AUTHENTICATION OF ANIMAL CELL CULTURE BY POLYMERASE CHAIN REACTION AMPLIFICATION AND DNA SEQUENCING - MERRY Y. LIU; SEH-CHING LIN; HSI LIU; FRANCISCO CANDAL; ABBAS VAFAI (In Vitro Cellular & Developmental Biology - Animal, 2003)

EXPRESSION OF SECRETED FRIZZLED-RELATED PROTEIN 2 IN A PRIMARY CANINE MAMMARY TUMOR CELL LINE: A CANDIDATE TUMOR MARKER FOR MAMMARY TUMOR CELLS - JIA-LIN LEE; CHING-JIN CHANG; LING-LING CHUEH; CHUNG-TIEN LIN (In Vitro Cellular & Developmental Biology - Animal, 2003)

EXPRESSION OF SECRETED FRIZZLED RELATED PROTEIN 2 IN A PRIMARY CANINE MAMMARY TUMOR CELL LINE: A CANDIDATE TUMOR MARKER FOR MAMMARY TUMOR CELLS - Jia-Lin Lee; Ching-Jin Chang; Ling-Ling Chueh; Chung-Tien Lin (In Vitro Cellular & Developmental Biology - Animal, 2003)

Characterization of CMS and maintainer lines in indica rice (Oryza sativa L.) based on RAPD marker analysis - Masahiko Ichii; De Lin Hong; Yoshinori Ohara; Chang Ming Zhao; Shin Taketa (Euphytica, 2003)

Trace Metals in Candle Smoke - T.-S. Lin; F.-M. Shen; J.-L. Chen; M.-H. Yang (Bulletin of Environmental Contamination and Toxicology, 2003)

H2 production with anaerobic sludge using activated-carbon supported packed-bed bioreactors - Kuo-Shing Lee; Yung-Sheng Lo; Yung-Chung Lo; Ping-Jei Lin; Jo-Shu Chang (Biotechnology Letters, 2003)

Plant regeneration through somatic embryogenesis from zygotic embryo-derived callus of Areca catechu L. (Arecaceae) - Hsiang-Chih Wang; Jen-Tsung Chen; Shieh-Ping Wu; Mei-Chun Lin; Wei-Chin Chang (In Vitro Cellular & Developmental Biology - Plant, 2003)

Involvement of the terminus of grouper betanodavirus capsid protein in virus-like particle assembly - M. W. Lu; C. S. Lin (Archives of Virology, 2003)

Hibiscus protocatechuic acid inhibits lipopolysaccharide-induced rat hepatic damage - Lin W.-L.; Hsieh Y.-J.; Chou F.-P.; Wang C.-J.; Cheng M.-T.; Tseng T.-H. (Archives of Toxicology, 2003)

Diagnosis of the Heavy Rain near a Meiyu Front Using the Wet Q Vector Partitioning Method - Coijun Yue; Shaowen Shou; Kaiping Lin; Xiuping Yao (Advances in Atmospheric Sciences, 2003)

Establishment of cell lines from a tropical grouper, Epinephelus awoara (Temminck & Schlegel), and their susceptibility to grouper irido‐ and nodaviruses - Y‐S Lai; J A C John; C‐H Lin; I‐C Guo; S‐C Chen; K Fang; C‐H Lin; C‐Y Chang (Journal of Fish Diseases, 2003)
Four tropical marine fish cell lines have been established from the eye, fin, heart and swim bladder of grouper, Epinephelus awoara (Temminck & Schlegel). Optimum media and temperature conditions for maximum growth were standardized. The eye and swim bladder cells were mostly epithelial, but the fin and heart cells were mostly fibroblastic. The viability of cells was 95% after 1 year of storage in liquid nitrogen (−196 °C). Besides these four cell lines, previously established grouper brain, kidney and liver cell lines were also used for a viral susceptibility study which showed that all the cell lines were sensitive to grouper iridovirus, whereas only brain, fin and liver cell lines were susceptible to the yellow grouper nervous necrosis virus (a nodavirus). Electron microscopy studies of the grouper irido‐ and nodaviruses in ultrathin sections of infected cells showed an abundance of viral particles in the cytoplasm of the virus‐infected cells indicating the effective replication of these two viruses. It is suggested that these cell lines can be used for the isolation of putative fish specific viruses and provide a valuable tool to study the mechanisms of host–pathogen interactions. Furthermore, these cell lines upon transfection, using pEGFP‐C1 and pEGFP‐aMT 2.5 (ayu metallothionein promoter), produced significant fluorescent signals indicating their utility for exogenous studies.